+0

# Please solve with all steps, thank you!

0
35
1
+39

(x-3)/3 = -4+(1/2)

#1
+4711
+1

$$\frac{x-3}{3}\,=\,-4+\frac12$$

Multiply both sides of the equation by  3  .

$$x-3\,=\,3(-4)+3(\frac12) \\~\\ x-3\,=\,-12+\frac32$$

Add  3  to both sides of the equation.

$$x\,=\,-12+\frac32+3$$

Get a common denominator on the right side and combine the fractions.

$$x\,=\,\frac{-12(2)}{2}+\frac{3}{2}+\frac{3(2)}{2} \\~\\ x\,=\,\frac{-24}{2}+\frac{3}{2}+\frac{6}{2} \\~\\ x\,=\,\frac{-24+3+6}{2}\\~\\ x\,=\,-\frac{15}{2}$$

hectictar  Oct 3, 2017
Sort:

#1
+4711
+1

$$\frac{x-3}{3}\,=\,-4+\frac12$$

Multiply both sides of the equation by  3  .

$$x-3\,=\,3(-4)+3(\frac12) \\~\\ x-3\,=\,-12+\frac32$$

Add  3  to both sides of the equation.

$$x\,=\,-12+\frac32+3$$

Get a common denominator on the right side and combine the fractions.

$$x\,=\,\frac{-12(2)}{2}+\frac{3}{2}+\frac{3(2)}{2} \\~\\ x\,=\,\frac{-24}{2}+\frac{3}{2}+\frac{6}{2} \\~\\ x\,=\,\frac{-24+3+6}{2}\\~\\ x\,=\,-\frac{15}{2}$$

hectictar  Oct 3, 2017

### 22 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details